Investigation on the Impact of Uncertified Contractors on Project Performance in the Northern Region of Malaysia - Law Joe Win; Abdul Halim A. Ghani (Recent Trends in Civil Engineering and Built Environment, 2021)
The performance of construction depends significantly on the capability of contractors. However, the prevailing construction industry faces a shortage of scarce and compatible contractors accompanying construction’s critical skills, causing construction failure, delay, and cost overrun. Thus, this study aims to identify the importance of a certificate, analyse the characteristic of uncertified contractors of Grade 1 to Grade 3 general contractors, and determine their effect on the project performance. A questionnaire survey was conducted and then analyzed using SPSS software. The mean value method and Relative Important Index (RII) method was used. Targeted respondents include managing directors, project managers, engineers, quantity surveyors, architects, and site supervisors working in the Northern Region of Peninsular Malaysia. The obtained result had employed both descriptive analysis and reliability analysis to achieve the study objective. The interpreted data shows that uncertified contractors do not understand fundamental theories applicable to construction sites (RII = 0.72). The lack of technological skills such as Artificial intelligence and the Internet of Things (RII = 0.758) for uncertified contractors also impact construction’s performance. Besides, delays in construction projects (RII = 0.452) were mainly the reason for the poor project performance by uncertified contractors. Consequently, this study could garner more attention towards contractors’ qualifications to ensure that all parties involved in construction are competent and professional.